Choosing your english - Haycraft, John; Creed, Terence
Can you express your moods and feelings in english? can you be angry or astonished ? Can you express delight, curiosity or despair ? Can you be warmly appreciative ? Can you choose your english ?
List of words.
Keywords: Communication; Langage